Quantification of Alterations in Cortical Bone Geometry Using Site Specificity Software in Mouse models of Aging and the Responses to Ovariectomy and Altered Loading - Galea, Gabriel L.; Hannuna, Sion; Meakin, Lee B.; Delisser, Peter J.; Lanyon, Lance E.; Price, Joanna S. (Frontiers in Endocrinology, 2015)
Investigations into the effect of (re)modelling stimuli on cortical bone in rodents normally rely on analysis of changes in bone mass and architecture at a narrow cross-sectional site. However, it is well established that the effects of axial loading produce site-specific changes throughout bones’ structure. Non-mechanical influences (e.g. hormones) can be additional to or oppose locally-controlled adaptive responses and may have more generalized effects. Tools currently available to study site-specific cortical bone adaptation are limited. Here we applied novel Site-Specificity software to measure bone mass and architecture at each 1% site along the length of the mouse tibia from standard micro-computed tomography (μCT) images. Resulting measures are directly comparable to those obtained through μCT analysis (R2 > 0.96). Site-Specificity Analysis was used to compare a number of parameters in tibiae from young adult (19-week-old) versus aged (19-month-old) mice; ovariectomized and entire mice; limbs subjected to short periods of axial loading or disuse induced by sciatic neurectomy. Age was associated with uniformly reduced cortical thickness and site-specific decreases in cortical area most apparent in the proximal tibia. Mechanical loading site-specifically increased cortical area and thickness in the proximal tibia. Disuse uniformly decreased cortical thickness and decreased cortical area in the proximal tibia. Ovariectomy uniformly reduced cortical area without altering cortical thickness. Differences in polar moment of inertia between experimental groups were only observed in the proximal tibia. Ageing and ovariectomy also altered eccentricity in the distal tibia. In summary, Site-Specificity Analysis provides a valuable tool for measuring changes in cortical bone mass and architecture along the entire length of a bone. Changes in the (re)modelling response determined at a single site may not reflect the response at different locations within the same bone.